Learning to work together – lessons from a reflective analysis of a research project on public involvement. Issue 1 (December 2017) - Howe, A.; Mathie, E.; Munday, D.; Cowe, M.; Goodman, C.; Keenan, J.; Kendall, S.; Poland, F.; Staniszewska, S.; Wilson, P.
Plain English summary Patient and public involvement (PPI) in research is very important, and funders and the NHS all expect this to happen. What this means in practice, and how to make it really successful, is therefore an important research question. This article analyses the experience of a research team using PPI, and makes recommendations on strengthening PPI in research. There were different PPI roles in our study – some people were part of the research team: some were on the advisory group; and there were patient groups who gave specific feedback on how to make research work better for their needs. We used minutes, other written documents, and structured individual and group reflections to learn from our own experiences over time. The main findings were:- for researchers and those in a PPI role to work in partnership, project structures must allow flexibility and responsiveness to different people's ideas and needs; a named link person can ensure support; PPI representatives need to feel fully included in the research; make clear what is expected for all roles; and ensure enough time and funding to allow meaningful involvement. Some roles brought more demands but also more rewards than others - highlighting that it is important that people giving up their time to help with research experience gains from doing so. Those contributing to PPI on a regular basis may want to learn new skills, rather than always doing the same things. Researchers and the public need to find ways to develop roles in PPI over time. We also found that, even for a team with expertise in PPI, there was a need both for understanding of different ways to contribute, and an evolving 'normalisation' of new ways of working together over time, which both enriched the process and the outputs. Abstract Background Patient and public involvement (PPI) is now an expectation of research funders, in the UK, but there is relatively little published literature on what this means in practice – nor is there much evaluative research about implementation and outputs. Policy literature endorses the need to include PPI representation at all stages of planning, performing and research dissemination, and recommends resource allocation to these roles; but details of how to make such inputs effective in practice are less common. While literature on power and participation informs the debate, there are relatively few published case studies of how this can play out through the lived experience of PPI in research; early findings highlight key issues around access to knowledge, resources, and interpersonal respect. This article describes the findings of a case study of PPI within a studyabout PPI in research. Methods The aim of the study was to look at how the PPI representatives' inputs had developed over time, key challenges and changes, and lessons learned. We used realist evaluation and normalisation process theory to frame and analyse the data, which was drawn from project documentation, minutes of meetings and workshops, field notes and observations made by PPI representatives and researchers; documented feedback after meetings and activities; and the structured feedback from two formal reflective meetings. Results Key findings included the need for named contacts who support, integrate and work with PPI contributors and researchers, to ensure partnership working is encouraged and supported to be as effective as possible. A structure for partnership working enabled this to be enacted systematically across all settings. Some individual tensions were nonetheless identified around different roles, with possible implications for clarifying expectations and deepening understandings of the different types of PPI contribution and of their importance. Even in a team with research expertise in PPI, the data showed that there were different phases and challenges to 'normalising' the PPI input to the project. Mutual commitment and flexibility, embedded through relationships across the team, led to inclusion and collaboration. Conclusion Work on developing relationships and teambuilding are as important for enabling partnership between PPI representatives and researchers as more practical components such as funding and information sharing. Early explicit exploration of the different roles and their contributions may assist effective participation and satisfaction.